Imaging findings of an isolated gastric tuberculosis case mimicking lymphoma and infiltrative gastric cancer - Bahadır Öztürk; Mehmet Selim Nural; Özgür Ecemiş; Murat Danacı (Turkish Journal of Gastroenterology, 2019)
-